Transformation of Phosphorus in Speciation and Bioavailability During Converting Poultry Litter to Biochar - Li, Wei; Feng, Xionghan; Song, Weiping; Guo, Mingxin (Frontiers in Sustainable Food Systems, 2018)
Converting poultry litter (PL) to biochar and applying the biochar to cropland as a soil amendment may be a best approach for recovering nutrients from solid biowastes while minimizing nutrient runoff losses from the treated field. To evaluate the potential of PL-derived biochar as a slow-release phosphorus (P) fertilizer, the speciation, lability, and bioavailability of P in PL and the derived biochars were examined and compared. Raw PL and its derived biochars through 300–600°C slow pyrolysis were analyzed for total P (TP), inorganic P (IP), and organic P (OP) contents. The TP was fractionated into readily, generally, moderately, low, and non-labile pools by sequential extraction with different solutions. The TP was further assessed for bioavailability using batch extraction by water, Olsen, Bray-1, Mehlich-3, and 1 M HCl extractants. The P species in biochars were characterized using solid-state 31P nuclear magnetic resonance (NMR) techniques. The results indicate that during pyrolysis OP in PL was transformed to IP and water-soluble P to low labile forms such as hydroxyapatite and oxyapatite especially at higher temperature. Bray-1 and Mehlich-3 were appropriate extractants for evaluating the immediate to medium-term available and the long-term available P in biochar, respectively. Converting PL to biochar through ≤450°C pyrolysis significantly reduced the water-soluble proportion and the lability of P but did not compromise the long-term P bioavailability, resulting in a P-enriched, slow release soil amendment that would minimize the P runoff risks following field application. The promising results need to be further validated in soil-biochar-plant systems.